A new species of the genus Notocupes from mid-Cretaceous Burmese amber (Coleoptera: Archostemata: Ommatidae). (April 2020) - Jiang, Zhuoyin; Li, Yingge; Song, Chengjun; Shi, Hongliang; Liu, Ye; Chen, Rui; Kong, Fanli
Abstract: A new ommatid beetle species, Notocupes denticollis sp. nov. is described based on a well-preserved male specimen in Cretaceous Burmese amber with the apex of the genitalia visible. The new species can be distinguished from other members of the genus by its pronotum with large denticles on the lateral margins. The male genitalia of the new species are unique among all other studied ommatids.